The bomb - Taylor, Theodore (Harcourt, 2007)
In 1944, when the Americans liberate Bikini Atoll from the Japanese, fourteen-year-old Sorry Rinamu does not realize that in two years he will lead a desperate effort to save his island home from a much more deadly threat.